Edukasi Perilaku Sexting Dalam Meningkatkan Pengetahuan Remaja di Kabupaten Bulukumba - Arfiani Arfiani; Fitriani Fitriani; Samila Samila; Yenny Sima (PPNI UNIMMAN, 2023)
: Indonesia, as a developing country, has a fairly large teenage population. The World Health Organization (WHO) states that teenagers are residents in the age range of 10-19 years. However, one of the developments in the industrial revolution 4.0 is a big leap in the information and communication technology sector. The development of technology among teenagers has triggered quite an increase in the use of smartphones so that it can influence teenage behavior, where teenagers also participate in sexting behavior, causing concern in various circles. The term sexting refers to the sending and receiving of sexual images through some form of virtual messaging where someone sends messages or material in the form of images and videos electronically, especially via smartphones, the internet and other electronic media. With the increasing number of teenagers and very complex teenage problems, especially the most prominent problem is teenage sexual behavior, which is the beginning of teenage reproductive health problems, this service aims to increase teenagers' knowledge about sexting behavior in order to avoid sexting behavior. The method used is a pre-test and post-test after health education regarding sexting behavior. The results show that the majority of teenagers' knowledge before counseling was less than 12 teenagers or 80%. Meanwhile, teenagers' knowledge before being given counseling was lowest at Good knowledge, namely 1 person or 6.67%. Teenagers' knowledge after counseling was highest in good knowledge, namely 14 people or 93.33%. This is an appropriate benchmark for the success of counseling.